Micro-expansion graphite-based composite negative electrode material and preparation method and application thereof

By introducing transition metal sulfides and polymers into the graphite negative electrode material and carbonization treatment, the problem of the layer peeling and rupture of the graphite negative electrode material during charging and discharging is solved, and the cycle performance and rate performance of the battery are significantly improved.

CN119905557AActive Publication Date: 2025-04-29ZHANJIANG JUXIN NEW ENERGY +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510051427.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-29
Estimated Expiration
2045-01-13

AI Technical Summary

Technical Problem

The existing graphite negative electrode materials are prone to shedding and rupture during charging and discharging, resulting in a sharp decline in battery capacity and diving in cycle life.

Method used

Micro-expanded graphite is used as the basis to generate transition metal sulfides by reaction with transition metal ions and sulfur sources, and polymerization is carried out using aromatic hydrocarbons and boron trifluoride to fix the transition metal sulfides in the inter-graphite structure and carbonization is carried out to enhance inter-layer binding force.

Benefits of technology

The first discharge capacity, first Coulomb efficiency, cycle performance and rate performance of the micro-expanded graphite-based composite anode material is significantly improved, ensuring the stability of the battery's performance after multiple charges and discharges.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005240070880000111
    Figure BDA0005240070880000111
Patent Text Reader

Abstract

The invention provides a micro-expanded graphite-based composite negative electrode material and a preparation method and application thereof.The preparation method comprises the steps that firstly, micro-expanded graphite is soaked in a solution containing transition metal ions, and the transition metal ions enter an interlayer structure of the micro-expanded graphite through diffusion; then reacting with a sulfur source at a high temperature to generate transition metal sulfide; finally, low-melting-point aromatic hydrocarbon substances enter an interlayer structure of the micro-expanded graphite in a molten state, and transition metal sulfide is more firmly fixed in the interlayer structure of the micro-expanded graphite while the aromatic hydrocarbon substances are catalyzed to polymerize through boron trifluoride; and the defects of partial decomposition, recombination, structural change and the like of the internal structure of the micro-expanded graphite under the influence of stress after multiple charge-discharge cycles are avoided. Furthermore, the existence of the hard carbon layer coating the outer surface of the inner core can further stabilize the layered structure of the inner core, so that the stable performance of the micro-expanded graphite in the charge-discharge process is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of negative electrode materials for lithium ion batteries, and in particular relates to a micro-expanded graphite-based composite negative electrode material and a preparation method and application thereof. Background Art

[0002] With the continuous development of new energy vehicles, energy storage and other industries, the new energy battery industry has been continuously upgraded, and the requirements for battery charging and discharging performance and energy density have also been continuously improved. As one of the four key materials of the battery, the negative electrode material has a significant impact on the battery's energy density, cycle performance, charge and discharge rate, and low-temperature discharge performance. Graphite is the most widely used and commercially used negative electrode material, mainly because graphite has relatively high capacity and conductivity, and it is cheap and easy to obtain.

[0003] It is known in the art that only by continuously improving the performance and technical level of negative electrode materials can we promote the progress and development of battery technology and meet higher requirements for application scenarios. Research has found that the interlayer space of graphite is both a lithium ion storage space and a solid phase diffusion channel for lithium ions; if the interlayer spacing of graphite is increased, the rate performance of graphite negative electrode materials can be improved.

[0004] In order to improve the rate problem of graphite negative electrode materials, the prior art usually expands graphite when preparing graphite negative electrode materials to expand the distance between graphite layers; however, the interlayer bonding force of graphite itself is poor, and the graphite structure is easily unstable after expansion treatment, and the co-insertion of solvent molecules is easy to occur, causing serious layer shedding and cracking problems of graphite negative electrode materials during charging and discharging. For this reason, the prior art usually uses asphalt and other substances to wrap the outer surface of expanded graphite, thereby limiting the volume expansion of expanded graphite during charging and discharging. However, there are many defects in this method. For example, macromolecular substances such as asphalt are difficult to penetrate into the expanded graphite, and the internal structure of the expanded graphite cannot be effectively protected. There are defects between the curled flake graphite layers inside the expanded graphite, resulting in weak bonding between the graphite layers. When the battery is charged and discharged too many times, the expanded graphite layer will still undergo partial peeling, reorganization and structural changes, etc. These changes will cause the battery capacity to decay sharply, and even the battery cycle life will drop. Summary of the invention

[0005] In order to improve the problem of poor cycle performance of graphite negative electrode materials in the prior art, the present invention provides a micro-expanded graphite-based composite negative electrode material and a preparation method and application thereof. The micro-expanded graphite-based composite negative electrode material prepared by the method has excellent first discharge capacity, first coulomb efficiency, cycle performance and rate performance.

[0006] The present invention provides the following technical solutions:

[0007] A method for preparing a micro-expanded graphite-based composite negative electrode material, the method comprising the following steps:

[0008] (1) mixing a metal salt solution of a transition metal element, micro-expanded graphite and sodium dodecylbenzene sulfonate, and heating to prepare a micro-expanded graphite / transition metal ion mixture;

[0009] (2) mixing the micro-expanded graphite / transition metal ion mixture of step (1) with a sulfur source under a protective atmosphere, reacting to prepare a micro-expanded graphite / transition metal sulfide composite material;

[0010] (3) mixing the micro-expanded graphite / transition metal sulfide composite material of step (2) and an aromatic hydrocarbon material by ball milling, adding the mixture into a reactor for polymerization reaction, and simultaneously introducing boron trifluoride gas into the reactor to prepare a micro-expanded graphite / transition metal sulfide / polymer composite material;

[0011] (4) The micro-expanded graphite / transition metal sulfide / polymer composite material of step (3) is mixed with a coating agent and subjected to carbonization treatment to prepare the micro-expanded graphite-based composite negative electrode material.

[0012] According to an embodiment of the present invention, in step (1), the transition metal element is at least one of tin, antimony, cobalt, iron, zinc, molybdenum and manganese.

[0013] According to an embodiment of the present invention, in step (1), the metal salt of the transition metal element is at least one of the nitrate, carbonate, sulfate and chloride of the transition metal element.

[0014] According to an embodiment of the present invention, in step (1), the shape of the micro-expanded graphite is at least one of spherical, potato-shaped and elliptical.

[0015] According to an embodiment of the present invention, in step (1), the median particle size D of the micro-expanded graphite is 50 5-15μm.

[0016] According to an embodiment of the present invention, in step (1), the interlayer spacing d(002) of the (002) crystal plane of the micro-expanded graphite is 0.3376nm-0.3396nm, for example, 0.3376nm, 0.3378nm, 0.3380nm, 0.3384nm, 0.3388nm, 0.3390nm, 0.3392nm, 0.3394nm or 0.3396nm.

[0017] According to an embodiment of the present invention, in step (1), the micro-expanded graphite can be prepared by methods known in the art, or purchased through commercial channels.

[0018] According to an embodiment of the present invention, in step (1), the concentration of the metal salt solution of the transition metal element is 0.1-1 mol / L, for example, 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L or 1 mol / L.

[0019] According to an embodiment of the present invention, in step (1), the mass ratio of the micro-expanded graphite to the metal salt solution of the transition metal element is 1:5-1:20, for example, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:11, 1:12, 1:13, 1:14, 1:15, 1:16, 1:17, 1:18, 1:19 or 1:20.

[0020] According to an embodiment of the present invention, in step (1), the mass ratio of sodium dodecylbenzene sulfonate to micro-expanded graphite is (1-5):100, for example, 1:100, 1.5:100, 2:100, 2.5:100, 3:100, 3.5:100, 4:100, 4.5:100 or 5:100.

[0021] According to an embodiment of the present invention, in step (1), the heating temperature is 50-100°C, for example, 50°C, 60°C, 70°C, 80°C, 90°C or 100°C; the heating time is 1-12 hours, for example, 1 hour, 2 hours, 3 hours, 5 hours, 6 hours, 8 hours, 10 hours or 12 hours. The heating is carried out under stirring conditions.

[0022] According to an embodiment of the present invention, in step (1), after the heating is completed, the mixed solution is preferably filtered, washed and dried to obtain a mixture of micro-expanded graphite / transition metal ions.

[0023] According to an embodiment of the present invention, in step (1), during the heating process, the transition metal ions can enter the interlayer structure of the micro-expanded graphite by diffusion or the like.

[0024] According to an embodiment of the present invention, in step (2), the protective atmosphere is, for example, a nitrogen atmosphere or an argon atmosphere.

[0025] According to an embodiment of the present invention, in step (2), the reaction temperature is 300-900°C, for example, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C or 900°C; the reaction time is 1-6 hours, for example, 1 hour, 2 hours, 3 hours, 5 hours or 6 hours.

[0026] According to an embodiment of the present invention, in step (2), the sulfur source is selected from at least one of thioacetamide, ammonium persulfate, thiourea, sodium sulfide and cysteine.

[0027] According to an embodiment of the present invention, in step (2), the mass ratio of the micro-expanded graphite / transition metal ion mixture to the sulfur source is 1:(1-3), for example, 1:1, 1:1.5, 1:2, 1:2.5 or 1:3.

[0028] According to an embodiment of the present invention, in step (2), during the reaction process, the transition metal ions react with the sulfur source to generate transition metal sulfides, which are loaded onto the interlayer structure of the micro-expanded graphite, which can not only effectively fill the defects in the interlayer structure of the micro-expanded graphite, but also improve the capacity of the prepared micro-expanded graphite-based composite negative electrode material.

[0029] According to an embodiment of the present invention, in step (3), the ball milling mixing time is 1-5 hours, for example, 2 hours, 3 hours or 4 hours; the ball milling mixing speed is 100-400 rpm, for example, 100 rpm, 200 rpm, 300 rpm or 400 rpm.

[0030] According to an embodiment of the present invention, in step (3), the aromatic hydrocarbon substance is selected from one or more of naphthalene, anthracene, phenanthrene, pyrene, coumarone resin and petroleum resin.

[0031] According to an embodiment of the present invention, in step (3), the mass ratio of the aromatic hydrocarbon substance to the micro-expanded graphite / transition metal sulfide composite material is (0.1-0.3):1, for example, 0.1:1, 0.15:1, 0.2:1, 0.25:1 or 0.3:1.

[0032] According to an embodiment of the present invention, in step (3), after the polymerization reaction is completed, it is preferably cooled to room temperature to prepare a micro-expanded graphite / transition metal sulfide / polymer composite material.

[0033] According to an embodiment of the present invention, in step (3), the temperature of the polymerization reaction is 150-300°C, for example, 150°C, 200°C, 250°C or 300°C; the time of the polymerization reaction is 1-10 hours, for example, 1 hour, 2 hours, 3 hours, 5 hours, 6 hours, 8 hours or 10 hours.

[0034] According to an embodiment of the present invention, in step (3), 10-30 ml of boron trifluoride gas is introduced per gram of aromatic hydrocarbon substance, for example, 10 ml, 12 ml, 15 ml, 18 ml, 20 ml, 22 ml, 24 ml, 25 ml, 28 ml or 30 ml of boron trifluoride gas is introduced.

[0035] According to an embodiment of the present invention, in step (3), during the polymerization reaction, aromatic hydrocarbon substances in a molten state enter the interlayer structure of the micro-expanded graphite, and boron trifluoride catalyzes the aromatic hydrocarbon substances to undergo a condensation reaction to generate a macromolecular polymer with a high molecular weight. At the same time, the generated macromolecular polymer has a high residual carbon value. The macromolecular polymer will be converted into amorphous carbon during the carbonization process. The amorphous carbon can more firmly fix the transition metal sulfide on the interlayer structure of the micro-expanded graphite, fill the defects of the interlayer structure of the expanded graphite, enhance the bonding force between the layers, and avoid the micro-expanded graphite after multiple charge and discharge cycles. Under the influence of stress, the internal structure of the micro-expanded graphite undergoes partial decomposition, reorganization, and structural changes, etc., and the stability of the micro-expanded graphite is significantly improved.

[0036] According to an embodiment of the present invention, in step (4), the coating agent is selected from one or more of coumarone resin, phenolic resin, glucose and epoxy resin.

[0037] According to an embodiment of the present invention, in step (4), the mass ratio of the coating agent to the micro-expanded graphite / transition metal sulfide / polymer composite material of step (3) is (3-10):100, for example, 3:100, 4:100, 5:100, 6:100, 7:100, 8:100, 9:100 or 10:100.

[0038] According to an embodiment of the present invention, in step (4), the temperature of the carbonization treatment is 800-1000°C, for example, 800°C, 850°C, 900°C, 950°C or 1000°C; the time of the carbonization treatment is 1-6 hours, for example, 1 hour, 2 hours, 3 hours, 5 hours or 6 hours.

[0039] According to an embodiment of the present invention, in step (4), the carbonization treatment is carried out in a nitrogen atmosphere or an argon atmosphere.

[0040] According to an embodiment of the present invention, in step (4), after the carbonization treatment is completed, the carbonization product is preferably dispersed to obtain a median particle size D 50 The invention is a micro-expanded graphite-based composite negative electrode material with a size of 5-15 μm.

[0041] According to an embodiment of the present invention, in step (4), the coating agent can be coated on the outer surface of the micro-expanded graphite / transition metal sulfide / polymer composite material, and the coating agent will form a hard carbon layer after carbonization treatment. The presence of the hard carbon layer can further stabilize the layered structure of the inner core (micro-expanded graphite / transition metal sulfide / amorphous carbon composite material) to ensure the stable performance of the micro-expanded graphite during the charging and discharging process.

[0042] The present invention also provides a micro-expanded graphite-based composite negative electrode material prepared by the method.

[0043] According to an embodiment of the present invention, the micro-expanded graphite-based composite negative electrode material has a core-shell structure, including a core and a shell layer, wherein the core is a composite material of micro-expanded graphite / transition metal sulfide / amorphous carbon, and the amorphous carbon fixes the transition metal sulfide on the interlayer structure of the micro-expanded graphite; and the shell layer is hard carbon.

[0044] According to an embodiment of the present invention, the median particle size D of the micro-expanded graphite-based composite negative electrode material is 50 5-15μm.

[0045] According to an embodiment of the present invention, the mass ratio of the micro-expanded graphite to the transition metal sulfide in the micro-expanded graphite-based composite negative electrode material is 100:(1-4), for example, 100:1, 100:2, 100:3 or 100:4.

[0046] According to an embodiment of the present invention, the mass ratio of the micro-expanded graphite to the amorphous carbon in the micro-expanded graphite-based composite negative electrode material is 100:(0.5-2), for example, 100:0.5, 100:1, 100:1.5 or 100:2.

[0047] According to an embodiment of the present invention, the mass ratio of the micro-expanded graphite to the hard carbon in the micro-expanded graphite-based composite negative electrode material is 100:(1-4), for example, 100:1, 100:2, 100:3 or 100:4.

[0048] The present invention also provides the use of the micro-expanded graphite-based composite negative electrode material, which is used in lithium ion batteries, preferably used to prepare negative electrodes of lithium ion batteries.

[0049] The present invention also provides a negative electrode for a lithium ion battery, wherein the negative electrode comprises the above-mentioned micro-expanded graphite-based composite negative electrode material.

[0050] The present invention also provides a lithium ion battery, which comprises the above-mentioned micro-expanded graphite-based composite negative electrode material or the above-mentioned negative electrode for a lithium ion battery.

[0051] Beneficial effects of the present invention:

[0052] The present invention adopts micro-expanded graphite with controllable lamellar structure as the basis, firstly immerses the micro-expanded graphite in a solution containing transition metal ions, so that the transition metal ions enter the interlayer structure of the micro-expanded graphite by diffusion; then reacts with a sulfur source at high temperature to generate transition metal sulfide; finally, low-melting-point aromatic hydrocarbon substances are used to enter the interlayer structure of the micro-expanded graphite in a molten state, and the transition metal sulfide is more firmly fixed in the interlayer structure of the micro-expanded graphite while catalyzing the polymerization of the aromatic hydrocarbon substances by boron trifluoride, thereby filling the defects of the interlayer structure of the expanded graphite, enhancing the bonding force between the layers, and avoiding the defects of the micro-expanded graphite internal structure partially decomposed, reorganized and structurally changed under the influence of stress after multiple charge and discharge cycles. Furthermore, the presence of a hard carbon layer coated on the outer surface of the inner core can further stabilize the layered structure of the inner core, thereby ensuring the stable performance of the micro-expanded graphite during the charge and discharge process.

[0053] The present invention cleverly loads transition metal sulfides onto the interlayer structure of micro-expanded graphite. The transition metal sulfides with good rigidity fill the defects of the interlayer structure of micro-expanded graphite and enhance the structural stability. Moreover, after being applied to batteries, the transition metal sulfides can provide embedding and detachment sites for lithium ions, thereby improving the capacity of the battery. DETAILED DESCRIPTION

[0054] The preparation method of the present invention will be described in further detail below in conjunction with specific examples. It should be understood that the following examples are only exemplary illustrations and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.

[0055] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods; the reagents, materials, etc. used in the following examples, unless otherwise specified, can be obtained from commercial channels.

[0056] The micro-expanded graphite used in the following examples and comparative examples is spherical in shape, and the interlayer spacing d(002) of the (002) crystal plane of the micro-expanded graphite used in the following examples and comparative examples is 0.3382 nm.

[0057] Example 1

[0058] (1) adding 10 g of zinc chloride solution (0.2 mol / L) to 1 g of micro-expanded graphite, and then adding 0.02 g of sodium dodecylbenzene sulfonate, stirring at 60° C. for 6 hours, filtering, washing, and drying the mixture to obtain a micro-expanded graphite / zinc ion mixture;

[0059] (2) under a nitrogen atmosphere, mixing 1 g of the micro-expanded graphite / zinc ion mixture obtained in step (1) with 1.5 g of thiourea, heating to 600° C. and keeping the temperature for 2 h to obtain a micro-expanded graphite / zinc sulfide composite material;

[0060] (3) After mixing 1 g of the micro-expanded graphite / zinc sulfide composite material obtained in step (2) and 0.1 g of naphthalene by ball milling (150 rpm) for 5 hours, the mixture was placed in a reactor and heated to 180° C., and then 1.5 ml of boron trifluoride gas was introduced into the reactor to carry out polymerization reaction for 6 hours, and the mixture was cooled to room temperature to obtain a micro-expanded graphite / zinc sulfide / polymer composite material;

[0061] (4) 1 g of the micro-expanded graphite / zinc sulfide / polymer composite material obtained in step (3) was mixed with 0.03 g of phenolic resin, and carbonized at 900° C. for 6 hours under a nitrogen atmosphere to obtain the micro-expanded graphite-based composite negative electrode material.

[0062] The micro-expanded graphite-based composite negative electrode material has a core-shell structure, including a core and a shell layer, wherein the core is selected from a composite material of micro-expanded graphite / zinc sulfide / amorphous carbon, and the amorphous carbon fixes transition metal sulfide on the interlayer structure of the micro-expanded graphite; and the shell layer is hard carbon.

[0063] Example 2

[0064] (1) adding 6 g of tin chloride solution (0.15 mol / L) to 1 g of micro-expanded graphite, and then adding 0.03 g of sodium dodecylbenzene sulfonate, stirring at 70° C. for 8 hours, filtering, washing, and drying the mixture to obtain a micro-expanded graphite / tin ion mixture;

[0065] (2) under a nitrogen atmosphere, mixing 1 g of the micro-expanded graphite / tin ion mixture obtained in step (1) with 1.2 g of thioacetamide, heating to 500° C. and keeping the temperature for 2 h to obtain a micro-expanded graphite / tin sulfide composite material;

[0066] (3) After mixing 1 g of the micro-expanded graphite / tin sulfide composite material obtained in step (2) and 0.15 g of anthracene by ball milling (250 rpm) for 3 hours, the mixture was placed in a reactor and heated to 160° C., and then 1.0 ml of boron trifluoride gas was introduced into the reactor to carry out polymerization reaction for 10 hours, and the mixture was cooled to room temperature to obtain a micro-expanded graphite / tin sulfide / polymer composite material;

[0067] (4) 1 g of the micro-expanded graphite / tin sulfide / polymer composite material obtained in step (3) was mixed with 0.05 g of epoxy resin, and carbonized at 850° C. for 8 hours under a nitrogen atmosphere to obtain the micro-expanded graphite-based composite negative electrode material.

[0068] The micro-expanded graphite-based composite negative electrode material has a core-shell structure, including a core and a shell layer, wherein the core is selected from a composite material of micro-expanded graphite / tin sulfide / amorphous carbon, and the amorphous carbon fixes transition metal sulfide on the interlayer structure of the micro-expanded graphite; and the shell layer is hard carbon.

[0069] Example 3

[0070] (1) adding 10 g of cobalt chloride solution (0.3 mol / L) to 1 g of micro-expanded graphite, and then adding 0.01 g of sodium dodecylbenzene sulfonate, stirring at 80° C. for 4 hours, filtering, washing, and drying the mixture to obtain a micro-expanded graphite / cobalt ion mixture;

[0071] (2) under an argon atmosphere, mixing 1 g of the micro-expanded graphite / cobalt ion mixture obtained in step (1) with 2 g of ammonium persulfate, heating to 500° C. and keeping the temperature for 6 h to obtain a micro-expanded graphite / cobalt sulfide composite material;

[0072] (3) After mixing 1 g of the micro-expanded graphite / cobalt sulfide composite material obtained in step (2) and 0.2 g of naphthalene by ball milling (300 rpm) for 2 hours, the mixture was placed in a reactor and heated to 240° C., and then 1.8 ml of boron trifluoride gas was introduced into the reactor to carry out polymerization reaction for 6 hours, and the mixture was cooled to room temperature to obtain a micro-expanded graphite / cobalt sulfide / polymer composite material;

[0073] (4) 1 g of the micro-expanded graphite / cobalt sulfide / polymer composite material obtained in step (3) and 0.05 g of a phenolic resin coating agent were mixed, and carbonized at 1000° C. for 4 hours under a nitrogen atmosphere to obtain the micro-expanded graphite-based composite negative electrode material.

[0074] The micro-expanded graphite-based composite negative electrode material has a core-shell structure, including a core and a shell layer, wherein the core is selected from a composite material of micro-expanded graphite / cobalt sulfide / amorphous carbon, and the amorphous carbon fixes transition metal sulfide on the interlayer structure of the micro-expanded graphite; and the shell layer is hard carbon.

[0075] Example 4

[0076] (1) adding 10 g of zinc chloride solution (0.1 mol / L) to 1 g of micro-expanded graphite, and then adding 0.03 g of sodium dodecylbenzene sulfonate, stirring at 60° C. for 6 hours, filtering, washing, and drying the mixture to obtain a micro-expanded graphite / zinc ion mixture;

[0077] (2) under a nitrogen atmosphere, mixing 1 g of the micro-expanded graphite / zinc ion mixture obtained in step (1) with 1.8 g of thiourea, heating the mixture to 680° C. and keeping the temperature for 2 h to obtain a micro-expanded graphite / zinc sulfide composite material;

[0078] (3) After mixing 1 g of the micro-expanded graphite / zinc sulfide composite material obtained in step (2) and 0.15 g of naphthalene by ball milling (100 rpm) for 2 hours, the mixture was placed in a reactor and heated to 180° C., and then 1.5 ml of boron trifluoride gas was introduced into the reactor for polymerization reaction for 6 hours, and the mixture was cooled to room temperature to obtain a micro-expanded graphite / zinc sulfide / polymer composite material;

[0079] (4) 1 g of the micro-expanded graphite / zinc sulfide / polymer composite material obtained in step (3) and 0.03 g of a phenolic resin coating agent were mixed, and carbonized at 900° C. for 6 hours under a nitrogen atmosphere to obtain the micro-expanded graphite-based composite negative electrode material.

[0080] The micro-expanded graphite-based composite negative electrode material has a core-shell structure, including a core and a shell layer, wherein the core is selected from a composite material of micro-expanded graphite / zinc sulfide / amorphous carbon, and the amorphous carbon fixes transition metal sulfide on the interlayer structure of the micro-expanded graphite; and the shell layer is hard carbon.

[0081] Comparative Example 1

[0082] (1) adding 10 g of zinc chloride solution (0.2 mol / L) to 1 g of micro-expanded graphite, and then adding 0.02 g of sodium dodecylbenzene sulfonate, stirring at 60° C. for 6 hours, filtering, washing, and drying the mixture to obtain a micro-expanded graphite / zinc ion mixture;

[0083] (2) under a nitrogen atmosphere, mixing 1 g of the micro-expanded graphite / zinc ion mixture obtained in step (1) with 1.5 g of thiourea, heating to 600° C. and keeping the temperature for 2 h to obtain a micro-expanded graphite / zinc sulfide composite material;

[0084] (3) 1 g of the micro-expanded graphite / zinc sulfide composite material obtained in step (2) was mixed with 0.03 g of phenolic resin, and carbonized at 900° C. for 6 hours under a nitrogen atmosphere to obtain the micro-expanded graphite-based composite negative electrode material.

[0085] The micro-expanded graphite-based composite negative electrode material has a core-shell structure, including a core and a shell layer, wherein the core is selected from a micro-expanded graphite / zinc sulfide composite material, and transition metal sulfide is loaded on the interlayer structure of the micro-expanded graphite; and the shell layer is hard carbon.

[0086] Comparative Example 2

[0087] 1 g of micro-expanded graphite and 0.03 g of phenolic resin were mixed and carbonized at 900° C. for 6 hours under a nitrogen atmosphere to obtain the micro-expanded graphite-based composite negative electrode material.

[0088] The micro-expanded graphite-based composite negative electrode material has a core-shell structure, including a core and a shell layer, the core is selected from micro-expanded graphite, and the shell layer is hard carbon.

[0089] Comparative Example 3

[0090] (1) After 1 g of micro-expanded graphite and 0.4 g of naphthalene were ball-milled (150 rpm) for 5 hours, the mixture was placed in a reactor and heated to 180° C., 6 ml of boron trifluoride gas was introduced into the reactor, and the polymerization reaction was carried out for 6 hours. The mixture was cooled to room temperature to obtain a micro-expanded graphite / polymer composite material;

[0091] (2) 1 g of the micro-expanded graphite / polymer composite material obtained in step (1) was mixed with 0.03 g of phenolic resin, and carbonized at 900° C. for 6 hours under a nitrogen atmosphere to obtain the micro-expanded graphite-based composite negative electrode material.

[0092] The micro-expanded graphite-based composite negative electrode material has a core-shell structure, including a core and a shell layer, wherein the core is selected from a composite material of micro-expanded graphite / amorphous carbon, and the amorphous carbon is fixed on the interlayer structure of the micro-expanded graphite; and the shell layer is hard carbon.

[0093] Electrochemical performance test:

[0094] Semi-electric test method: The micro-expanded graphite-based composite negative electrode material prepared in the embodiment and the comparative example: conductive carbon black (SP): carboxymethyl cellulose (CMC): styrene-butadiene rubber (SBR) = 95:1:1.5:2.5 (mass ratio) was mixed evenly and applied on the copper foil. The coated electrode was placed in a 120°C vacuum drying oven for 12 hours. The simulated battery assembly was carried out in a Braun glove box protected by argon gas. The electrolyte was 1M-LiPF6+EC:DEC:DMC (volume ratio was 1:1:1), and the metal lithium sheet was the counter electrode. The simulated battery test was carried out in a 5V, 1000mA Xinwei battery test cabinet. The charge and discharge voltage was 0.01-1.5V, and the charge and discharge rate was 0.1C. The 0.1C first discharge capacity and 0.1C first coulomb efficiency obtained by the test were listed in Table 1.

[0095] Full battery test method: The micro-expanded graphite-based composite negative electrode material prepared in the embodiment and the comparative example is used as the negative electrode, lithium cobalt oxide is used as the positive electrode, and 1M-LiPF6+EC:DEC:DMC (volume ratio 1:1:1) solution is used as the electrolyte to assemble a full battery, and the charge and discharge at room temperature are carried out at a rate of 1C, and the voltage range is 3.0-4.2V. The cycle performance (capacity retention rate of 1000 cycles at room temperature 1C) obtained by the test is listed in Table 1. Rate performance: 0.1, 0.2, 0.4, 0.8 and 1.0A·g -1 After the current density reached 0.1A·g -1 When testing capacity, efficiency is maintained.

[0096] Table 1 Electrochemical performance test results

[0097]

[0098] Compared with Examples 1-4, Comparative Example 1 does not use low-melting-point aromatic hydrocarbon substances to treat the micro-expanded graphite / transition metal sulfide, which will cause the migration or aggregation of transition metal sulfides during the charge and discharge process, resulting in poor overall structural stability of the prepared micro-expanded graphite-based composite negative electrode material, and reduced cycle performance and rate performance.

[0099] In Comparative Example 2, only phenolic resin is used to coat the micro-expanded graphite. Since the phenolic resin cannot penetrate into the interior of the micro-expanded graphite, the internal structure of the micro-expanded graphite cannot be effectively protected. The resulting micro-expanded graphite composite negative electrode material has weak bonding between the curled flake graphite layers. When the battery is charged and discharged too many times, the micro-expanded graphite layer will peel off, reorganize, and change its structure, resulting in a decrease in the cycle performance and rate performance of the battery.

[0100] In Comparative Example 3, only low-melting-point aromatic hydrocarbons are used to treat the micro-expanded graphite. The rigidity of the amorphous carbon is low, and the interlayer structure of the micro-expanded graphite will partially collapse during the charge and discharge process, causing structural changes, thereby making the overall structural stability of the prepared micro-expanded graphite-based composite negative electrode material poor, and the cycle performance and rate performance are reduced. In addition, since no transition metal sulfide is introduced in Comparative Examples 2 and 3, the capacity of the obtained micro-expanded graphite composite negative electrode material decreases.

[0101] The above is an explanation of the embodiments of the present invention. However, the present invention is not limited to the above embodiments. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a micro-expanded graphite-based composite negative electrode material, the method comprising the following steps: (1) mixing a metal salt solution of a transition metal element, micro-expanded graphite and sodium dodecylbenzene sulfonate, and heating to prepare a micro-expanded graphite / transition metal ion mixture; (2) mixing the micro-expanded graphite / transition metal ion mixture of step (1) with a sulfur source under a protective atmosphere, reacting to prepare a micro-expanded graphite / transition metal sulfide composite material; (3) mixing the micro-expanded graphite / transition metal sulfide composite material of step (2) and an aromatic hydrocarbon material by ball milling, adding the mixture into a reactor for polymerization reaction, and simultaneously introducing boron trifluoride gas into the reactor to prepare a micro-expanded graphite / transition metal sulfide / polymer composite material; (4) The micro-expanded graphite / transition metal sulfide / polymer composite material of step (3) is mixed with a coating agent and subjected to carbonization treatment to prepare the micro-expanded graphite-based composite negative electrode material.

2. The preparation method according to claim 1, wherein In step (1), the transition metal element is at least one of tin, antimony, cobalt, iron, zinc, molybdenum and manganese; And / or, in step (1), the metal salt of the transition metal element is at least one of the nitrate, carbonate, sulfate and chloride of the transition metal element; And / or, in step (1), the interlayer spacing d(002) of the (002) crystal plane of the micro-expanded graphite is 0.3376nm-0.3396nm; And / or, in step (1), the concentration of the metal salt solution of the transition metal element is 0.1-1 mol / L; And / or, in step (1), the mass ratio of the micro-expanded graphite to the metal salt solution of the transition metal element is 1:5-1:20; And / or, in step (1), the mass ratio of sodium dodecylbenzene sulfonate to micro-expanded graphite is (1-5):100; And / or, in step (1), the heating temperature is 50-100° C.; the heating time is 1-12 hours.

3. The preparation method according to claim 1 or 2, wherein In step (2), the reaction temperature is 300-900° C. and the reaction time is 1-6 hours; And / or, in step (2), the sulfur source is selected from at least one of thioacetamide, ammonium persulfate, thiourea, sodium sulfide and cysteine; And / or, in step (2), the mass ratio of the micro-expanded graphite / transition metal ion mixture to the sulfur source is 1:(1-3).

4. The preparation method according to any one of claims 1 to 3, wherein: In step (3), the aromatic hydrocarbon substance is selected from one or more of naphthalene, anthracene, phenanthrene, pyrene, coumarone resin and petroleum resin; And / or, in step (3), the mass ratio of the aromatic hydrocarbon substance to the micro-expanded graphite / transition metal sulfide composite material is (0.1-0.3):1; And / or, in step (3), the polymerization reaction temperature is 150-300° C.; the polymerization reaction time is 1-10 hours; And / or, in step (3), 10-30 ml of boron trifluoride gas is introduced per gram of aromatic hydrocarbon substance.

5. The preparation method according to any one of claims 1 to 4, wherein: In step (4), the coating agent is selected from one or more of coumarone resin, phenolic resin, glucose and epoxy resin; And / or, in step (4), the mass ratio of the coating agent to the micro-expanded graphite / transition metal sulfide / polymer composite material of step (3) is (3-10):100; And / or, in step (4), the temperature of the carbonization treatment is 800-1000° C.; the time of the carbonization treatment is 1-6 hours.

6. A micro-expanded graphite-based composite negative electrode material prepared by the method according to any one of claims 1 to 5.

7. The micro-expanded graphite-based composite negative electrode material according to claim 6, wherein: The micro-expanded graphite-based composite negative electrode material has a core-shell structure, including a core and a shell layer, wherein the core is a composite material of micro-expanded graphite / transition metal sulfide / amorphous carbon, and the amorphous carbon fixes the transition metal sulfide on the interlayer structure of the micro-expanded graphite; and the shell layer is hard carbon.

8. The micro-expanded graphite-based composite negative electrode material according to claim 6 or 7, wherein: The mass ratio of micro-expanded graphite to transition metal sulfide in the micro-expanded graphite-based composite negative electrode material is 100:(1-4); And / or, the mass ratio of micro-expanded graphite to amorphous carbon in the micro-expanded graphite-based composite negative electrode material is 100:(0.5-2); And / or, the mass ratio of micro-expanded graphite to hard carbon in the micro-expanded graphite-based composite negative electrode material is 100:(1-4).

9. A negative electrode for a lithium ion battery, the negative electrode comprising the micro-expanded graphite-based composite negative electrode material according to any one of claims 6 to 8.

10. A lithium ion battery, comprising the micro-expanded graphite-based composite negative electrode material according to any one of claims 6 to 8 or the negative electrode for a lithium ion battery according to claim 9.

Citation Information

Patent Citations

  • Lithium-sulfur electric current producing cell

    CN105745778A

  • Lithium ion secondary battery

    JP2008010316A

  • Composite carbon material of negative electrode in lithuim ion battery and its preparation method

    US20090136849A1

  • Dry coating processes for substrates

    US20130260136A1

  • Production process for graphene-enabled bi-polar electrode and battery containing same

    US20210111391A1